Infective Endocarditis in a Patient of End-stage Kidney Disease and the Nuances of Management - Arun Prabhahar Rajarajan; Alan Shaji; Jasmine Sethi; Gowri Shankar; Harsimran Bhatia; Soumitra Ghosh (Indian Journal of Kidney Diseases)
Nontunneled central venous catheters remain an irreplaceable tool for initiation of haemodialysis in most patients with end-stage kidney disease (ESKD) in the developing and underdevelpoed countries. The low cost and convenience of insertion outweigh their disadvantage of higher rates of infection and mortality. We report a case of right-sided infective endocarditis (IE) in a ESKD patient secondary to uncuffed dialysis catheter and the challenges faced with respect to diagnosing and managing IE in such population. This case is unique because it demonstrates septic pulmonary emboli secondary to tricuspid valve Staphylococcus aureus IE in a patient with ESKD.